Exponential stability of discrete switched delay system via new discrete type inequality - Tipcha J. (2014)
In this paper, we propose to study a class of discrete-time nonlinear switched system with multiple delays. We shall give sufficient conditions which ensure global exponential stability of the switched system by using results on asymptotic behavior of difference equations as well as results on global exponential stability of difference equations by using discrete inequalities. © 2011 IEEE.